A Study on the Relation between Immigrant Language Maintenance and Language Ideology - Mihyon Jeon(전미현); Daehee Kim(김대희) (열린정신 인문학 연구, 23(1), 2022)
The purpose of this study is to seek the correlation between the language maintenance and language ideology of immigrants based on a review of the concepts of language loss, maintenance, and revitalization regarding language shift and reversing language shift. In order to understand what happens when two or more languages come into contact in a specific context, attention should be paid to three dimensions: language maintenance, loss, and language reactivation. Language maintenance refers to the continuous use of a specific language by a specific language community. Language loss means that a specific language-speaking group no longer uses the language. Language revitalization is an attempt to add a new language form or social function to minority languages with the aim of increasing the use of a specific language. Revitalization of language is related to reversing language shift. In considering the process of maintenance and revitalization of language, the issue of power relations is crucial. In order to understand the process of language shift and maintenance, it is necessary to understand the relationship of power. Also, in the study of language loss, maintenance, and revitalization, it is essential to understand the concept of language ideology alongside an awareness of the relationship of power. Language ideology can contribute to the legalization of the existing relations of power in which linguistic resources are verified in some societies and invalidated in others. The form of language ideology held by members of society can be formed by the existing relations of power. KCI Citation Count: 0